Ratio Legis Penetapan Pembayar Pajak (Taxpayer) sebagai Kedudukan Hukum dalam Pengujian Undang-Undang oleh Mahkamah Konstitusi - M. Yasin Al Arif; Hasanuddin Muhammad (The Constitutional Court of the Republic of Indonesia, 2020)
The discourse regarding the determination of the taxpayer standing in judicial review is not a completely new issue to be analyzed. However, it still needs to be examined in the framework of exploring the legal ratio for determining taxpayer standing in judicial review by the Constitutional Court. The findings of this research are an inseparable part of legal research in doctoral degree regarding the dynamics of the Petitioner’s legal standing in judicial review by the Constitutional Court. This research specifically answers the following questions: (a) how is the taxpayer doctrine as a legal standing in judicial review? (b) What is the legal ratio for determining taxpayer standing in judicial review by the Constitutional Court? This is normative legal research, by analyzing secondary data in the form of statutory regulations, Constitutional Court decisions, and literature related to the doctrine of the taxpayer standing in judicial review. The results indicate that the legal ratio for determining taxpayer standing in a judicial review can be traced through the legal considerations of the Constitutional Court decisions in judicial review since 2003-2019.